Anemia in relation to body mass index among female students of North Kerala: a pilot study - Thamban, Veena; Venkatappa, Kavana G.; K., Swarnalatha P.; M., Sparshadeep E. (International Journal of Research in Medical Sciences, 2018)
Background: Anemia among women causes many serious health problems and is pervasive in developing country. Many research studies have documented that malnutrition affects body growth and development, especially during the crucial period of adolescence. The association between anemia and body mass index (BMI) is a measure of nutrition and health status of adults. Aim was to study the association between anemia and BMI among female students. Methods: An observational study was conducted among first year medical and dental female students (n=109) aged 18-20years. Hemoglobin (Hb) levels (g/dL) by Sahli’s hemoglobinometer and BMI (kg/m2) were estimated. Anemia was defined as Hb content <12g/dL. Subjects were classified by BMI categories as underweight (BMI <18.5kg/m2), normal weight (BMI:18.5-24.99kg/m2), overweight (BMI ≥25kg/m2) and obesity (BMI ≥30kg/m2) according to WHO. Then the relation between anemia and BMI were statistically analyzed. Results: Overall, 48.62% female students were anemic. Of which 43.4% were underweight, 22.6% normal weight and 34.5% were above normal weight (over weight and obese). Mean value of hemoglobin was significantly decreased in underweight and overweight compared to normal weight (p<0.001). Anemia was significantly associated with BMI (χ2 =46.48, p=0.000). Conclusions: The study concludes the occurrence of anemia in both undernourished and over-nourished individuals which were significantly associated. Further studies are needed with larger sample size to document the factors that may be associated with anemia in females.